Dual plasmonic‐enhanced bulk‐heterojunction solar cell incorporating gold nanoparticles into solution‐processed anode buffer layer and active layer. Issue 2 (7th January 2015) - Zhou, Li; Yang, Jinya; Zhou, Ye; Han, Su‐Ting; Huang, Longbiao; Yan, Yan; Roy, V. A. L.
<x xml:space="preserve">Abstract</x> A dual plasmonic resonance effect on the performance of poly(3‐hexylthiophene) (P3HT):phenyl C61‐butyricacid methyl ester (PC61BM) based polymer solar cells (PSCs) has been demonstrated by selectively incorporating 25 nm colloidal gold nanoparticles (Au NPs) in a solution‐processed molybdenum oxide (MoO3) anode buffer layer and 5 nm colloidal Au NPs in the active P3HT:PCBM layer. The devices exhibit up to ∼20% improvement in power conversion efficiency which is attributed to the dual effect of localized surface plasmon resonance (LSPR) of Au NPs with enhanced light absorption and exciton generation. Our report shows a guideline on the usage of dual LSPR effect for the solution‐processed polymer solar cells to achieve high efficiencies. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)